Curriculum Approaches in English Language Teaching in Indonesia - Mubaroq, Syahrul; Qamariah, Zaitun (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2024)
This study used library research research methods to investigate curriculum approaches in English language teaching in Indonesia. The purpose of this study is to identify curriculum approaches commonly used in English language teaching in Indonesia and to understand how these approaches shape teaching methods and strategies applied in language classrooms. In this study, the author conducted a comprehensive literature review of relevant literature, including textbooks, research journals, articles, and education policies related to English language teaching in Indonesia. The data collected were analyzed qualitatively to identify curriculum approaches commonly used in the context of English language teaching in Indonesia. The results of this study show that some curriculum approaches commonly used in English teaching in Indonesia include content-based approaches, communicative approaches, task-based approaches, and grammar-based approaches. The selection of this curriculum approach is based on the goals and objectives of the program, as well as the needs and interests of learners. In conclusion, in Indonesia, English teaching is influenced by various curriculum approaches, which shape the methods and strategies applied in language classes. The choice of curriculum approach in English language teaching depends on the goals and objectives of the program, as well as the needs and interests of learners. Different approaches can be used in combination to create a comprehensive and effective language learning experience so that language learners can easily master the language in a formal setting.